Glottodydaktyczne kontakty polonistyki pekińskiej i warszawskiej .......... 37 - Kajak, Piotr (70 lat polonistyki Pekińskiego Uniwersytetu Języków Obcych: Dziedzictwo, rozwój, innowacje, 2025)
GLOTTODIDACTIC CONTACTS BETWEEN POLISH STUDIES IN BEIJING AND WARSAWThis text outlines the history of contacts between Warsaw and Beijing based on Polish Studies program’s past. The author refers to the tradition of teaching Polish as a foreign language at the reborn University of Warsaw and presents Chinese influences in the Polish philology and glottodidactic tradition of the capital’s university.